2020
DOI: 10.7759/cureus.8749
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Intubation Biomechanics: Intubation Forces Are Greater in Male Than in Female Patients, Independent of Body Weight

Abstract: Background Studies of head, neck, and cervical spine morphology and tissue material properties indicate that cervical spine biomechanics differ between adult males and females. These differences result in sex-specific cervical spine kinematics and injury patterns in response to standardized loading conditions. Because direct laryngoscopy and endotracheal intubation require the application of a load to the cervical spine, intubation biomechanics should be sex-specific. The aim of this study was to determine if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Studies on the correlation between gender and difficult airway found that difficult airway is encountered more commonly in males than females. [24] In our study, we found a slight increase in difficult airway among male patients, which agrees with the literature (p<0.05). The cervical vertebra, muscle, and soft-tissue volume are larger in men than women, even after adjusting for various body sizes, including total body weight.…”
Section: Discussionsupporting
confidence: 93%
“…Studies on the correlation between gender and difficult airway found that difficult airway is encountered more commonly in males than females. [24] In our study, we found a slight increase in difficult airway among male patients, which agrees with the literature (p<0.05). The cervical vertebra, muscle, and soft-tissue volume are larger in men than women, even after adjusting for various body sizes, including total body weight.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is likely related to reduce upper airway size and increased Mallampati score and laryngoscopy grade in older population [ 39 , 40 ]. Although male sex is associated with higher Mallampati score [ 40 ], upper airway collapsibility [ 39 ], and intubation forces [ 41 ], our analysis showed higher percentage of males correlated with increased rate of successful intubation and reduced rate of adverse events. Females have different upper airway anatomy, physiology, and biomechanics compared to males [ 39 , 41 43 ].…”
Section: Discussionmentioning
confidence: 87%
“…The 4-parameter linear regression model included the common intercept and 3 factors: laryngoscope (binary variable [Macintosh 1 and Airtraq 0]), percent glottic opening (continuous variable), and their interaction (the main factor of interest). For estimation of parameters, in our previous study of maximum intubation forces, 6 there were 3 of 101 observations that were mild outliers, exceeding the upper inner fence, and 1 of 101 extreme outliers, exceeding the outer inner fence. b Therefore, as done in the earlier study, 6 both least-squares linear regression and robust regression were used, the latter to account for outliers.…”
Section: Methodsmentioning
confidence: 98%
“…For estimation of parameters, in our previous study of maximum intubation forces, 6 there were 3 of 101 observations that were mild outliers, exceeding the upper inner fence, and 1 of 101 extreme outliers, exceeding the outer inner fence. b Therefore, as done in the earlier study, 6 both least-squares linear regression and robust regression were used, the latter to account for outliers. If the sample size was large, robust regression would be more suitable than least-squares regression because of the outliers.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation